Short-term IPO performance (underpricing) and its determinants of ChiNext stocks - Lie, Yaoxin (2018)
This paper follows short-term performance (underpricing) of initial public offerings (IPOs) of the growth enterprises market (GEM) in China (i.e, ChiNext) and investigates the determinants. Based on a sample of 314 enterprises launching through this market in a four-year period from June 2014 to June 2018, it reports holding returns at the close of the 1st trading day, 1st week, 2nd week, 1st month, 3rd month, 6th month, 9th month and 1st year after these companies going public. It finds that due to the unique characteristic of daily price cap (44% for the first trading day and 10% other trading days) in China, monitoring initial returns of first trading day as previous studies seems become less meaningful when all new stocks are capped by 44% at first day. Therefore, it puts the stress of research on the first day when the price of a single stock is not capped to go up, and it also analyses short-term IPO performance and its determinants. It points out that IPOs of ChiNext have high underpicing level. Using two-sample mean-comparison test and regression analysis, it tests the impact of third party certificate and identifies determinants for different points of holding timing. Finally, it concludes that issuance characteristics play important role in affecting degree of IPO underpricing, and firm characteristics cannot be ignored if investors plan to buy and hold ChiNext IPOs. Age of firm, issue price, the number of shares issued and turnover exchange rate have negative impact on underpricing degree. Contrary to this, firm size, ROA and growth of sales, are positively related.